THE ROLE OF GRAMMATICAL COHESION IN THE TEXT QUALITY AMONG JORDANIAN EFL STUDENTS IN EXPOSITORY ESSAYS - Khaled Salem Ahmad Amayreh; Ahmad Taufik Hidayah Abdullah, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The present paper shares interest that many scholars and linguists have highlighted in investigating the relationship between writing quality and grammatical cohesion devices. The aim of this study is to find out the relationship between the use of grammatical cohesive devices on the overall quality of expository essays produced by EFL fourth-year undergraduate students majoring in the English language at the Department of English language and literature Hashemite University in Jordan. It seeks to determine the efficacy of academic writing by Jordanian EFL students. Thirty purposive samples of compositions were collected and analyzed by the researcher to measure the relationship between the score of the writing quality and the grammatical cohesion devices in students' writing based on (1) analytical scale Jacob et al., (1981), and (2) Halliday and Hasan (1976) taxonomy of grammatical cohesion. The results showed that grammatical cohesive devices did not constitute a statistically significant correlation with the score of writing quality. It also revealed that the EFL students' written compositions were not successful due to their incapability to utilize the different forms of grammatical cohesive devices and their lack of knowledge about effectively using these devices in their academic writing.